Upaya Guru PAI dalam Mengatasi Efek Negatif Media Sosial terhadap Perilaku Peserta Didik di Tingkat Sekolah Menengah Pertama - Rahim Rahim; Sulaiman Sulaiman (AS-SABIQUN, 2022)
This study aims to identify and describe the efforts made by Islamic Religious Education Teachers at the SMP Pembangunan Laboratorium Universitas Negeri Padang (UNP) to overcome the negative effects of social media on the behavior of class VII students. This study uses a qualitative research methodology with a case study approach. Principals, Islamic Religious Education Teachers, Guidance and Counseling Teachers, and students of SMP Pembangunan Laboratorium Universitas Negeri Padang were the subjects of observation and interviews in this study. According to research, social media is generally used by seventh grade students at SMP Pembangunan Laboratorium Universitas Negeri Padang such as WhatsApp, Instagram, TikTok and YouTube. The widespread use of social media has a negative impact on student behavior, including disrespectful language, bullying, forgetting time, and a decreased social sense. With Dhuha prayer activities, one day one verse, and tadarus Al-qur'an, Islamic Religious Education Teachers at the SMP Pembangunan Laboratorium UNP are trying to overcome the negative effects of social media on students.